Death by chocolate pumpkin muffin - Graves, Sarah, 1951- (Graves, Sarah, 1951- Death by chocolate mystery, 2025)
"Decorations of cobwebs and creatures are just being taken down across Eastport's picturesque houses as the community says farewell to Halloween and ushers in winter with the unique confectionaries found only at the Chocolate Moose. Revelers have gathered on the waterfront for a party at local celebrity Hank Rafferty's ramshackle mansion, known as Stone House. The home repair TV show star and his guests await a devilish dessert delivery from Jake and Ellie--who arrive just after Hank's body falls to his death from the house's turret's balcony. Despite his show's popularity, Hank was not exactly beloved in Eastport, prompting the police to conduct a homicide investigation. Their number one suspect is the temperamental boyfriend of police chief Lizzie Snow, whom Hank openly hit on during the party. Although he may be hotheaded, Lizzie doesn't believe her boyfriend is capable of killing anyone. And neither do Jake and Ellie. Plenty of people had motive to want Hank dead--a disillusioned admirer, a school bully, and a discontented wife among them. Did any of them take the murderous plunge, or is there another ghost in Hank's shady past yet to be revealed?"--